CogniLock : Bridging Cognitive Threat Insights and AI Sentinel Defence - Thakre, Bhakti; Sheikh, Mahek; Charde, Rutuj; Bhajipale, Akansha (International Journal on Advanced Computer Engineering and Communication Technology, 2025)
In the rapidly evolving digital landscape, individuals and organizations face an increasing range of identity-based and cognitive cyber threats such as credential leaks, impersonation, and social media exploitation. Traditional cybersecurity solutions primarily focus on enterprise network defence, leaving a critical gap in personalized, intelligent protection mechanisms. This paper presents CogniLock, a SaaS-based cybersecurity framework that bridges cognitive threat intelligence with an AI-driven sentinel defines system. CogniLock operates through two primary phases: a Threat Intelligence Dashboard and a Digital Firewall. The dashboard aggregates and visualizes real-time malicious Indicators of Compromise (IOC) include IP addresses, URLs, domain names, and file hashes from reliable sources such as Alien Vault OTX, Abuse IPDB, and URL Haus. The Digital Firewall, on the other hand, offers proactive personal security modules such as email breach detection, password strength and exposure assessment, LinkedIn impersonation monitoring through cognitive similarity matching, and integrated reporting tools for social media abuse via official cyber complaint portals. By combining cognitive analytics with automated AI defences, CogniLock improves situational awareness and enables users to identify, address, and react to identity-threats cyber threats efficiently. The proposed framework contributes toward establishing an intelligent, adaptive, and user-centric model for modern digital protection.